Neonatal Surgery Case Fatality and Associated Factors in a Cuban Pediatric Hospital, 2005-2015. - Broche-Candó, Regla C.; Sosa-Palacios, Oramis; Morales-Mesa, Eduardo; Pla-Ampudia, Mirtha; Reyes-Romero, Oneida; Pérez-Moré, María Antonia (MEDICC Review)
INTRODUCTION Newborns in need of surgery are a challenge to manage and require highly specialized centers with multidisciplinary surgical teams. Since the 1980s, neonatal surgical survival has increased by up to 70% in some countries, mainly due to advances in neonatal intensive care, anesthesia and surgical technique. OBJECTIVE Describe surgical case fatality and survival in a neonatal reference hospital in Cuba, estimate risk of death, and identify potential risk predictors among neonatal characteristics. METHODS A retrospective cohort study was conducted based on hospital administrative data and clinical records for a series of surgical cases in the neonatal intensive care unit of Havana’s William Soler University Children’s Hospital from January 2005 to December 2015. All neonates who underwent surgery during the study period were included. The dependent variable was discharge status (alive, deceased); independent variables were: sex, age (in days) at time of surgery, gestational age, birth weight, indication for surgery, surgical order (first, repeat), and presence of sepsis or other postoperative complications. The study used contingency tables to analyze associations between neonatal characteristics and discharge status. A classification tree was used to obtain simple estimates of surgical risk. RESULTS Survival was 91.3% (675/739) among 739 neonates who underwent surgery. The majority were male (58.7%, 434/739), full term (84.2%, 622/739), and of normal birth weight (80.6%, 596/739). Most surgeries were performed in the first 10 days of life. Digestive system anomalies constituted the most common surgical indication (57.6%, 426/739); among these anorectal malformations (26.8%, 114/426) and esophageal atresia (17.4%, 74/426) predominated. Survival rates were lower for digestive perforation (57.7%, 15/26), gastroschisis (57.1%, 4/7) and intestinal atresia (73%, 27/37). Neonates in the youngest and oldest age groups at time of surgery faced highest risk of death, especially those in the older group. Term infants with normal birth weight operated on for the first time had survival rates >95%. CONCLUSIONS Survival was high and low birth weight conferred the worst prognosis. Infants with normal birth weight operated on for the first time had the greatest probability of survival.